2017
DOI: 10.1159/000475783
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leakage after Upper Gastrointestinal Surgery: Endoscopic Treatment

Abstract: Anastomotic leakages substantially influence the outcome of patients after major surgery of the upper gastrointestinal tract. Endoscopy is important for making a diagnosis and for managing anastomotic leakages. By means of endoscopic inspection of the anastomotic site, not only the size and position of dehiscences but also the blood supply of the anastomotic region and an imminent leakage can be assessed. To close anastomotic leakages, several therapeutic methods are available, i.e. stenting, clipping, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 12 publications
(13 reference statements)
1
31
0
2
Order By: Relevance
“…Together with pulmonary complications, leakage is the main factor responsible for increasing postoperative mortality and prolonging hospital stay [42 -44]. The actual therapeutic gold standard of postoperative esophageal leakage is the placement of SEMS [22], although promising results have also been published with EVT [45]. Whereas many studies can be found in the literature indicating the effectiveness of these techniques, prospective studies between the two treatments are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Together with pulmonary complications, leakage is the main factor responsible for increasing postoperative mortality and prolonging hospital stay [42 -44]. The actual therapeutic gold standard of postoperative esophageal leakage is the placement of SEMS [22], although promising results have also been published with EVT [45]. Whereas many studies can be found in the literature indicating the effectiveness of these techniques, prospective studies between the two treatments are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomot ic le a ks are a serious complication after resection of esophago-gastric cancer, occurring between 2.9 and up to 30% of patients [1][2][3]. Most often, leaks occur 3-5 days after surgery, and are associated with prolonged stay in intensive care unit and increased mortality [4]. In general, postoperative complications are predictors of worse overall and disease-specific survival [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endoscopic intervention is the therapy of choice. Depending on the size of leak, different endoscopic techniques, such as clips, fibrin glue, self-expandable metal stents, or, recently introduced, endoscopic vacuum therapy are used [4]. The choice of endoscopic technique often depends on local expertise and personal predilection only.…”
Section: Introductionmentioning
confidence: 99%
“…a profound knowledge of the interdisciplinary management of these severe postoperative complications [1][2][3][4][5][6]. Each of the medical specialties has its limitations and very special indications regarding the treatment of anastomotic leakages.…”
mentioning
confidence: 99%
“…Kähler [1] reports on a variety of endoscopic methods for the treatment of gastroesophageal anastomotic leakages: fibrin glue, clipping, stenting, and endoscopic vacuum-assisted closure system. Providing a correct indication is crucial, and technical success of esophageal stenting in the management of esophageal anastomotic leaks and benign esophageal perforations can be expected in more than 90%, while clinical success rates reach up to 81% [7].…”
mentioning
confidence: 99%